PREVALENCE OF CORONARY ARTERY DISEASE IN PATIENTS WITH END STAGE RENAL DISEASE WITH HIGHER CONCENTRATION OF TOTAL HOMOCYSTEINE CONCENTRATION IN BLOOD PLASMA - Dr. Ashwini K. Nigam; Dr. Prabhat K. Agrawal; Dr. Subhash Chandra; Dr. Ashish Gautam; Dr. Jitendra Doneria (Medico Research Chronicles, 1970)
The chronic kidney disease stage 3 to 5 (Glomerular filtration Rate GFR 59 to <15), Renal tubular dysfunction and decreased GFR which leads to decreased renal catabolism of homocysteine. Cardiovascular disease (CVD) is a major cause of death both in general population and in End Stage Renal Disease (ESRD), it accounts approx 40%. An analytical cross-sectional study is designed to find out the prevalence of coronary artery disease in patients with hyperhomocysteinemia in end renal disease patients and to discover the correlation between them. The homocysteine concentrations were found 34.66 ± 1.69 µmol/L and 17.6 ± 1.4 µmol/L for the group of patients with and without evidence of Coronary Artery Disease (CAD) respectively. Whereas the mean homocysteine concentrations of the total population were found 24.8 ± 1.85 µmol/L. This showed that patients having higher values of homocysteine concentration in blood plasma have higher chances of having CAD (p<0.050).